Evaluation of sarcopenia in patients with hyperthyroidism - TUFAN ÇİNÇİN, ASLI; ENGİN, EBRU; ELBASAN, ONUR; ILGIN, CAN (My University, 2022)
Background and aim: Sarcopenia is a generalized skeletal muscle disease and thyroid hormones have regulatory effects on skeletal muscle metabolism. This study aims to evaluate the association between hyperthyroidism and sarcopenia. Methods: Thirteen patients with overt hyperthyroidism (OH), 13 patients with subclinical hyperthyroidism (SH) and 30 healthy volunteers were included. OH was defined as serum thyroid-stimulating hormone (TSH) 1.12 ng/dL and/or free T3 (fT3) >4.37 ng/L; while SH was defined as TSH <0.34 when fT4 and fT3 were within the normal reference range (0.61-1.12 ng/dL for fT4; 2.6-4.37 ng/L for fT3). Handgrip strength (HGS) measurement and chair stand test were performed for muscle strength, while skeletal muscle mass index measurement with bioelectrical impedance analysis and calf circumference (CC) measurement were performed for muscle mass evaluation. Results: The median age was 44.9 (21-76), and 16 (61.5%) were female. HGS and CC were found to be significantly lower in the OH and SH groups than in the control group (p=0.007; p=0.008, respectively). Sarcopenia was more common in the OH and SH groups than in the control group (p=0.007), and the risk of sarcopenia was higher in the OH group than in the SH group (OR: 2.44, 95% CI: 0.26-31.87). In hyperthyroid patients, a high fT4 increased the possibility of sarcopenia (OR: 6.0 95% CI: 0.59-79.23). Conclusions: Sarcopenia is significantly more common in patients with hyperthyroidism.
Keywords: Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Sağlık Bilimleri; Mühendislik ve Teknoloji; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Food Engineering; Health Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Tarım Bilimleri; BESLENME VE DİYETETİK; GIDA BİLİMİ VE TEKNOLOJİSİ; Agriculture & Environment Sciences (AGE); AGRICULTURAL SCIENCES; NUTRITION & DIETETICS; FOOD SCIENCE & TECHNOLOGY; Yemek bilimi; Yaşam Bilimleri; Beslenme ve Diyetetik; Food Science; Life Sciences; Hyperthyroidisim; muscle; sarcopenia